Seroprevalence of IgG antibodies against Anaplasma marginale in cattle from south Mozambique Soroprevalência de anticorpos de classe IgG contra Anaplasma marginale em bovinos da região Sul de Moçambique - António Amélia Mucalane Tembue; Jenevaldo Barbosa da Silva; Fábio Jorge Moreira da Silva; Marcus Sandes Pires; Cristiane Divan Baldani; Cleber Oliveira Soares; Carlos Luiz Massard; Adivaldo Henrique da Fonseca (Revista Brasileira de Parasitologia Veterinária, 2011)
The current study aimed to investigate the seroprevalence of IgG antibodies to Anaplasma marginale in cattle from Maputo, Gaza and Inhambane provinces, south Mozambique. A total of 809 serum samples from cattle were obtained and tested by indirect enzyme-linked immunosorbent assay (i-ELISA). The chi-square test at 5% significance was used to assess the association between seroprevalence and the variables gender, age and geographic origin of animals. The overall seropositivity was 76.5% (n = 619) and anti-A. marginale antibodies were detected in 89.1% (n = 156), 68.4% (n = 308) and 84.2% (n = 155) of the animals in the provinces of Maputo, Gaza and Inhambane, respectively. A significant association (p < 0.05) was found with the geographic origin of the animals, while sex had no significant relationship. The frequencies of seropositive in the age groups were 63.2% (n = 72), 80.0% (n = 92), 83.1% (n = 98) and 77.3% (n = 357) for animals <12; >12 and <24; >24 and <36; >36 months, respectively. These results indicate that in southern Mozambique there are areas of enzootic stability to A. marginale. Thus, epidemiological monitoring is required to monitor the immune status of animals in the region. O objetivo do presente estudo foi investigar a soroprevalência de anticorpos da classe IgG contra Anaplasma marginale em bovinos de corte da região Sul de Moçambique. Para esse efeito, 809 amostras de soro foram coletadas e avaliadas pelo ensaio imunoadsorção enzimático indireto (ELISA-i). O teste Qui-Quadrado, a 5% de significância, foi utilizado para avaliar a associação entre a soroprevalência e as variáveis sexo, idade e origem geográfica dos animais. A soropositividade geral foi de 76,5% (n = 619), e anticorpos anti-A. marginale foram detectados em 89,1% (n = 156), 68,4% (n = 308) e 84,2% (n = 155) dos animais nas províncias de Maputo, Gaza e Inhambane, respectivamente. Uma associação significativa (p < 0,05) foi observada entre a origem geográfica dos animais, enquanto o sexo não demonstrou uma relação significativa. A frequência de soropositivos com relação à faixa etária foi de 63,2% (n = 72), 80,0% (n = 92), 83,1% (n = 98) e 77,3% (n = 357) para animais de <12; >12 a <24; >24 <36; >36 meses, respectivamente. Os resultados demonstram que, no Sul de Moçambique, existem áreas de estabilidade enzoótica para A. marginale, em animais maiores de 12 meses. Assim, monitoramento epidemiológico deve ser realizado para o acompanhamento do status imunológico dos animais na região.